Landscape suitability evaluation as a tool for development and protection of valuable rural areas - Tomić, Dora (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
This research studied application possibilities of landscape suitability evaluation as a methodological approach within landscape planning. It was presented in the case study of the wider area of Krka River through analysis of three Mediterranean agricultural crops. Results indicated (1) the efficacy of the procedure for obtaining optimised spatial potential for development as well as protection of valuable rural areas and (2) the possibility to include new methods into current planning regulations.
Keywords: Croatia; environmental protection; Hrvaška; Krka (reka); podeželje; prostorsko planiranje; rural area; spatial planning; sustainable development; trajnostni razvoj; varstvo okolja